Repeated Induced-Membrane Technique Failure without Infection: A Series of Three Consecutive Procedures Performed for a Single Femur Defect. (8th August 2020) - Mathieu, Laurent; Durand, Marjorie; Demoures, Thomas; Steenman, Christian; Masquelet, Alain-Charles; Collombet, Jean-Marc
Abstract : A 40-year-old male was treated using the induced-membrane technique (IMT) for a noninfected, 9 cm long femoral bone defect complicating a lengthening procedure. The interesting case feature lies in the three consecutive IMT procedures that were necessary to achieve complete bone repair in this unusual clinical situation. The first procedure failed because of the lack of graft revascularization likely related to an induced-membrane (IM) alteration demonstrated by histological observations. The second IMT procedure led to partial graft integration interrupted by the elongation nail breakage. At last, the third procedure fully succeeded after nail exchange and iterative iliac bone grafting. Complete bone union was achieved with a poor functional recovery one year after the last procedure and four years following the first cement spacer implantation. By means of clinical and histological observations, we demonstrated that the first and the second IMT failures had two distinct origins, namely, biological and mechanical causes, respectively. Although simple, a successful IMT procedure is not so easy to complete.